Regimes of the World (RoW): Opening New Avenues for the Comparative Study of Political Regimes - Lührmann, Anna (2018)
Classifying political regimes has never been more difficult. Most contemporary regimes hold de-jure multiparty elections with universal suffrage. In some countries, elections ensure that political rulers are—at least somewhat—accountable to the electorate whereas in others they are a mere window dressing exercise for authoritarian politics. Hence, regime types need to be distinguished based on the de-facto implementation of democratic institutions and processes. Using V-Dem data, we propose with Regimes of the World (RoW) such an operationalization of four important regime types—closed and electoral autocracies; electoral and liberal democracies—with vast coverage (almost all countries from 1900 to 2016). We also contribute a solution to a fundamental weakness of extant typologies: The unknown extent of misclassification due to uncertainty from measurement error. V-Dem’s measures of uncertainty (Bayesian highest posterior densities) allow us to be the first to provide a regime typology that distinguishes cases classified with a high degree of certainty from those with “upper” and “lower” bounds in each category. Finally, a comparison of disagreements with extant datasets (7%–12% of the country-years), demonstrates that the RoW classification is more conservative, classifying regimes with electoral manipulation and infringements of the political freedoms more frequently as electoral autocracies, suggesting that it better captures the opaqueness of contemporary autocracies.